Lattice distortion leads to glassy thermal transport in crystalline Cs 3 Bi 2 I 6 Cl 3 - Zezhu Zeng; Zheyong Fan; Michele Simoncelli; Chen Chen; Ting Liang; Yue Chen; Geoff Thornton; Bingqing Cheng (Proceedings of the National Academy of Sciences, 2025)
The glassy thermal conductivities observed in crystalline inorganic perovskites such as Cs 3 Bi 2 I 6 Cl 3 are perplexing and lacking theoretical explanations. Here, we first experimentally measure its thermal transport behavior from 20 to 300 K, after synthesizing Cs 3 Bi 2 I 6 Cl 3 single crystals. Using path-integral molecular dynamics simulations driven by machine learning potentials, we reveal that Cs 3 Bi 2 I 6 Cl 3 has large lattice distortions at low temperatures, which may be related to the large atomic size mismatch. Employing the Wigner formulation of thermal transport, we reproduce the experimental thermal conductivities based on lattice-distorted structures. This study thus provides a framework for predicting and understanding glassy thermal transport in materials with strong lattice disorder.